URGENSI PENDIDIKAN KARAKTER - Kosim, Mohammad (STAIN PAMEKASAN, 2012)
AbstractCharacter education is a planned effort in helping someone to understand, care, and act based on ethical values / moral principles adopted. This paper seeks review of character education which is currently a major issue of national education. Several important issues are studied in this paper is about the meaning of character and character education, the reasons why education is important characters are developed, the foundation and source of character education, character values that need to be developed either in the form of universal values and the values unearthed a typical nation of religious values, Pancasila, the nations cultural and national education goals. This paper also describes the implementation of character education strategy needs to be done in a systematic, holistic, and sustainable within the family, school and wider community. Kata-kata kuncikarakter, pendidikan karakter, tujuan pendidikan nasional